2014
DOI: 10.1093/eurheartj/ehu050
|View full text |Cite
|
Sign up to set email alerts
|

Titin gene mutations are common in families with both peripartum cardiomyopathy and dilated cardiomyopathy

Abstract: Targeted NGS shows that potentially causal mutations in cardiomyopathy-related genes are common in families with both PPCM and DCM. This supports the earlier finding that PPCM can be part of familial DCM. Our cohort is particularly characterized by a high proportion of TTN mutations and a low recovery rate in PPCM cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(119 citation statements)
references
References 39 publications
1
105
1
6
Order By: Relevance
“…W Stanach Zjednoczonych oszacowana śmiertelność związana z kardiomiopatią okołoporodową wynosi 6-10% [703]. Najnowsze badania wskazują, że kardiomiopatia okołoporodowa może być klinicznym przejawem rodzinnej DCM związanej z mutacjami genów [704].…”
Section: Zaburzenia Rytmu Związane Z Kardiomiopatią Okołoporodowąunclassified
“…W Stanach Zjednoczonych oszacowana śmiertelność związana z kardiomiopatią okołoporodową wynosi 6-10% [703]. Najnowsze badania wskazują, że kardiomiopatia okołoporodowa może być klinicznym przejawem rodzinnej DCM związanej z mutacjami genów [704].…”
Section: Zaburzenia Rytmu Związane Z Kardiomiopatią Okołoporodowąunclassified
“…56 Two groups recently evaluated rare pedigrees of patients affected by both PPCM and DCM and identified variants in genes encoding myofibrillar proteins, including TTN, the gene encoding the sarcomere protein titin. 118,119 Whether similar variants would be found in common, sporadic PPCM remains uncertain.…”
Section: Geneticsmentioning
confidence: 99%
“…After these findings, the same group collected 18 more families with PPCM and DCM from various countries and found that titin gene (TTN) mutations were the most common variant among the families. 25 In another study from the USA, Morales et al made similar observations in a large cohort study. Of 4,110 women from 520 pedigrees in the familial DCM database, 45 cases of PPCM were identified.…”
Section: Ppcm and Dcmmentioning
confidence: 64%